Strength Training and Development in Competitive Speed Skating - Stuart, A.; Cochrane-Snyman, K. C. (Strength and Conditioning Journal, 2022)
Speed skating is a time trial-based sport that requires skill, strength, power, and capacity. The unique demands of the sport require a thorough need analysis to better understand the physical requirements, potential injuries, and periodization to successfully prepare athletes. This article will focus on the overall development of the short-distance to middle-distance speed skater to provide coaches, athletes, and strength and conditioning professionals an understanding of the biomechanical, physiological, and energy system demands of the sport and to identify common injuries that are sustained from repeated efforts.